Drone x-ray / Nurul Izzati Iwani Zulkafli ... [et al.] - Zulkafli, Nurul Izzati Iwani; Zulkifli, Siti Nursyafikah; Mohamed Fauzi, Siti Sarah; Mohd Ali, Nur Syafiqah; Jazlan, Raihanah (2017)
X- Ray examinations are widely used in health sectors as a tool to help doctors to diagnose a disease. Due to the importance of x- ray examination and high demand towards the patients, x-ray machine should be flexible to ease the radiographer to perform the best radiography. The current mobile x-ray machine is heavy and bulky to handle and sometimes can injure the radiographer due to non-ergonomic posture when handling the x-ray machine. This product is suitable in preventing radiographers exposed to possible injury and unsafe environment.